Docetaxel-induced ichthyosiform eruption following third cycle of chemotherapy in oropharyngeal carcinoma: a case report - Brar, Balvinder Kaur; Geetika,; Brar, Sukhmani Kaur (International Journal of Basic & Clinical Pharmacology, 2026)
Docetaxel is a taxane chemotherapeutic agent associated with various dermatologic adverse effects. Ichthyosiform eruption is a rare and often underrecognized cutaneous manifestation of docetaxel therapy. We report the case of a 61-year-old female patient with oropharyngeal carcinoma who developed a generalized ichthyosiform eruption after receiving her third cycle of docetaxel-based chemotherapy. The patient presented with widespread dry, scaly skin resembling a fish-scale pattern. Laboratory investigations including thyroid function tests and lipid profile were within normal limits. The patient was not on statin therapy or other medications known to cause ichthyosiform eruptions. A diagnosis of docetaxel-induced ichthyosiform eruption was established based on clinical presentation, temporal relationship with chemotherapy, and exclusion of other etiologies. The patient was managed conservatively with intensive emolliation and keratolytic agents with subsequent improvement. Ichthyosiform eruption is a rare but clinically significant adverse effect of docetaxel chemotherapy that can impact patient quality of life. Clinicians should be aware of this presentation to facilitate early recognition and appropriate management. This case adds to the limited literature on this uncommon dermatologic toxicity and emphasizes the importance of systematic evaluation to exclude metabolic and drug-induced causes of acquired ichthyosis.